2009
DOI: 10.1523/jneurosci.3431-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and Precise Neuronal Firing during Sensory Plasticity in Superficial Layers of Primary Somatosensory Cortex

Abstract: Neocortical neurons show astonishing variation in the presence and timing of action potentials across stimulus trials, a phenomenon whose function and significance has been the subject of great interest. Here we present data showing that this response variability can be significantly reduced by altered sensory experience. Removal of all but one whisker from the side of the mouse face results in the rapid (within 24 h) potentiation of mean firing rates within the cortical representation of the spared whisker in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…This result is consistent with electrophysiological data of Benedetti et al (2009), who showed that removing of all but one whisker on one side of the snout results in the potentiation of stimulus-evoked firing in layer 2/3 neurons within the cortical representation of the spared whisker in adolescent mice after 7 days of deprivation. We did not observe further increase in c-Fos expression after 28 days of deprivation, which suggests that enhancement of the spared whiskers input reaches its maximum level already after 7 days of deprivation.…”
Section: Enhancement Of Response In the Spared Barrel Columnssupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with electrophysiological data of Benedetti et al (2009), who showed that removing of all but one whisker on one side of the snout results in the potentiation of stimulus-evoked firing in layer 2/3 neurons within the cortical representation of the spared whisker in adolescent mice after 7 days of deprivation. We did not observe further increase in c-Fos expression after 28 days of deprivation, which suggests that enhancement of the spared whiskers input reaches its maximum level already after 7 days of deprivation.…”
Section: Enhancement Of Response In the Spared Barrel Columnssupporting
confidence: 92%
“…Potentiation of layer IV neurons responses in spared barrels was not observed with extracellular recordings in urethane anesthesia (Benedetti et al 2009). As with the 2-DG method, a significant proportion of the label is ascribed to synaptic activity (Schwartz et al 1979;Nudo and Masterton 1986), the signal in layer IV may originate from thalamocortical axons (Lu¨bke et al 2003;Meyer et al 2010), and interbarrel connections or from axons of layer IV making synapses on basal dendrites of layers II/III neurons (Meyer et al 2010).…”
Section: Enhancement Of Response In the Spared Barrel Columnsmentioning
confidence: 99%
“…and certain patterns of neuronal activity in the sensory system. In contrast to this notion, previous studies in visual cortex have found high variability in spike counts to repeated stimulus presentations (Schiller et al, 1976;Tolhurst et al, 1983;Vogels et al, 1989;Buracas et al, 1998) (but see Gur et al, 1997;Kara et al, 2000;DeWeese et al, 2003;Amarasingham et al, 2006;Gur and Snodderly, 2006;Nawrot et al, 2008;Benedetti et al, 2009). In fact, the Fano factor (FF), the ratio of the variance of the spike counts across repetitions to the mean spike count, was often found to be higher than that of a random Poisson process, which has a FF of 1.…”
Section: Introductionmentioning
confidence: 83%
“…A number of studies have uncovered sub-Poissonian spike count variability in diverse cortical areas (DeWeese et al, 2003;Uzzell and Chichilnisky, 2004;Gur and Snodderly, 2006;Benedetti et al, 2009;Maimon and Assad, 2009). However, Poisson-type variability was shown by Beck et al (2008) to enable the brain to make optimal Bayesian decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation